The Informational City / Information Technology, Economic Restructuring, and the Urban-Regional Process - Castells Manuel (Blackwell, 1994)
A marvelous synthesis of research and trends affecting American cities. Acknowledgements, Introduction, The Informational Mode of Development and the Restructuring of Capitalism, The New Industrial Space: The Locational Pattern of Information-Technology Manufacturing and Its Effects on Spatial Dynamics, The Space of Flows: The Use of New Technologies in the Information Economy and the Dialectics between Centralization and Decentralization of Services, Information Technology and the Restructuring of Capital-Labor Relationships and the Rise of the Dual City, High Technology and the Transition from the Urban Welfare State, The Internationalization of the Economy and New Technologies and the Variable Geometry of the Spatial Structure, The Reconstruction of Social Meaning in the Space of Flows, Notes, Index.